Penerapan Pengkodean Data Base-64 dan Kode QR Citra Foto Wajah untuk Autentikasi Tanda Tangan Dokumen Digital dengan Library Javascript - Hana Afriliza; Febi Eka Febriansyah (Jurnal Pepadun, 2023)
The application of technology has an impact on replacing conventional methods with modern ones, one of which is providing document authentication. Signatures can be used as a solution in authenticating documents because they are considered capable of being used as mathematical proof that the document is not modified illegally. The difference that lies between the signature on digital documents and conventional documents is in terms of security. Signatures on conventional documents are prone to forgery. This is due to the absence of evidence to ensure that the document has been signed by the party concerned. Thus, the use of signatures on digital documents is more secure than on conventional documents. The security that is carried out to ensure its authenticity is by utilizing a QR code which contains an id, photo of the signatory which is encoded first using base-64 coding, and a link which is used to verify the authenticity of the document. The verification process carried out to ensure its authenticity is by scanning the QR code embedded in the document. The library developed using Javascript and Waterfall is used as a development method, and the testing method used is black-box testing.